Ảnh hưởng của nồng độ NH3 đến thành phần pha tinh thể và tính chất quang xúc tác của n-TiO2 - Thân, Lê Diên; Lương, Ngô Sỹ (Vietnam Journal of Chemistry, 2014)
Influence of NH3 concentration to phase component and photocatalytic of N-TiO2 has been reseached. Results showed that NH3 is orientation agents of the structure, promoted the formation of oxygen vacancies (V0) in crystalline N-TiO2, narrow band gap and increase photocatalytic activity under visible light of prepered products. The interaction of NH3 with Ti(IV) changed of electron structure and the condensation model of the precursor molecules, that  is cause of the phase component changing of the precipitation powder from rutils to anatase and amorphous. Experimental results showed that appropriate NH3/TiCl4 molar ratio for prepare N-TiO2 powder is 4.2. Keywords: N-TiO2, photocatalytic, oxygen vacancies, phase component.